Medical leadership, a systematic narrative review: do hospitals and healthcare organisations perform better when led by doctors? - Jeffrey Braithwaite; Kristiana Ludlow; Robyn Clay-Williams; Luke Testa; Zhicheng Li (BMJ Open)
Introduction Despite common assumptions that doctors are well placed to lead hospitals and healthcare organisations, the peer-reviewed literature contains little evidence on the performance of doctors in leadership roles in comparison with that of non-medical managers.Objectives To determine whether there is an association between the leader’s medical background and management performance in terms of organisational performance or patient outcomes.Methods We searched for peer-reviewed, English language studies using Medline, Embase and Emerald Management between 2005 and 2017. We included quantitative, qualitative and mixed method empirical studies on the performance of senior healthcare managers where participants were described as doctors or leaders and where comparative performance data were provided on non-medical leaders. Studies without full text available, or no organisational, leadership behaviour or patient measures, were excluded.Results The search, conducted in Medline (n=3395), Embase (n=1913) and Emerald Management (n=454) databases, yielded 3926 entries. After the application of inclusion and exclusion criteria, 16 studies remained. Twelve studies found that there were positive differences between medical and non-medical leaders, and eight studies correlated those findings with hospital performance or patient outcomes. Six studies examined the composition of boards of directors; otherwise, there were few common areas of investigation. Five inter-related themes emerged from a narrative analysis: the impact of medical leadership on outcomes; doctors on boards; contribution of qualifications and experience; the medical leader as an individual or part of a team and doctors transitioning into the medical leadership role.Discussion and conclusion A modest body of evidence supports the importance of including doctors on organisational governing boards. Despite many published articles on the topic of whether hospitals and healthcare organisations perform better when led by doctors, there were few empirical studies that directly compared the performance of medical and non-medical managers. This is an under-researched area that requires further funding and focus.